On the Foundations of the Property Rights Theory of the Firm: Cooperative Investments and Message-Dependent Contracts - Andreas Roider (University of Bonn, Bonn Graduate School of Economics (BGSE), 2000)
The property-rights theory assumes that trade is non-contractible ex-ante and focusses exclusively on the allocation of property-rights. We derive foundations for this focus on property-rights by identifying scenarios where only one of the simple ownership structures is optimal even though trade is contractible. In these scenarios it is optimal: (1) not to sign a trade contract; (2a) to sign a partially enforced trade contract; (2b) such a combination of asset ownership and a trade contract might even achieve the first-best. For the purpose of identifying the optimal simple ownership structure, trade contracts can be neclected in scenarios (2a) and (2b).
Keywords: D23; D82; L14; L22; 330; Incomplete Contracts; Property Rights; Specific Investments